Management of fenestration using bone allograft in conjunction with platelet-rich fibrin - Anuradha Bhatsange; Alkesh Shende; Sabina Deshmukh; Sharanabasappa Japatti (Wolters Kluwer Medknow Publications, 2017)
Fenestration and dehiscence are said to be anatomical variations of cortical bone and not true pathological entities. They represent window-like defects covered by periosteum and overlying gingiva with or without the intact marginal bone. The etiology of such defects is still unclear, though many hypotheses such as occlusal traumatism, trauma, and variation in root bone angulation have been put forward. Diagnosis of such defects is challenging clinically, and they cannot be appreciated in conventional radiographs. In many instances, they are accidentally discovered during periodontal and oral surgical procedures. These defects, if not treated, can affect prognosis and complicate healing of the affected teeth. Treatment of such cortical bony defects is challenging and involves the use of potential regenerative materials to aid in regeneration. This case report describes the successful management of such a defect, discovered through exploratory flap approach, using PRF in conjunction with bone allograft.